MRI of the Upper Extremity Elbow, Wrist, and Hand - Casagranda, Bethany U.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book systematically discusses the anatomy and pathology of three specific regions of the upper extremity: the elbow, wrist, and hand. Divided into three sections, by body part, chapters cover anatomy and pathology. The anatomy chapters give a comprehensive view of each body part and normal variants found there. Although the primary modality emphasized will be MRI, illustrations and other modalities, including plain radiograph and CT, will be used to comprehensively discuss the anatomy of each region. Liberally illustrated, the pathology chapters then cover both traumatic and non-traumatic causes for imaging and detail how to perform and interpret each MRI. Specific examples include: osseous trauma, soft tissue trauma, and tumor imaging. Chapters are written with the deliberate intention to be of value to all levels of radiology training while remaining a reliable resource for attending radiologists. .
Section I: Elbow -- Elbow Anatomy -- Elbow Pathology -- Section II: Wrist -- Wrist Anatomy -- Wrist Pathology -- Section III: Hand -- Hand Anatomy -- Hand Pathology.
Keywords: Radiology; Orthopedics; Radiology; Orthopaedics; Elbow -- diagnostic imaging; Wrist -- diagnostic imaging; Hand -- diagnostic imaging; Magnetic Resonance Imaging -- methods